Is it safe to remove the chest tube in the operating room after robotic lobectomy, segmentectomy, and wedge resection with lymphadenectomy? - McCormack, Ashley J.; Phillips, Katherine G.; Cerfolio, Robert J. (Frontiers in Surgery, 2025)
BackgroundWe have previously shown that it is safe to remove chest tubes within four hours after robotic pulmonary resection with aggressive thoracic lymphadenectomy in patients without an air leak.MethodsThis is a prospective quality improvement study that examines the process of removing chest tubes before the patient leaves the operating room (OR) after robotic pulmonary resection. Chest tubes were removed in the OR if the air leak was ≤75 mL/min on a digital drainage system. The tubes were reinserted only for oxygen desaturations from increasing pneumothorax and/or increasing subcutaneous emphysema.ResultsBetween 1 March 2023 and 12 December 2024, 223 consecutive patients underwent pulmonary resection with complete lymphadenectomy by one surgeon. Overall, 130 patients (58%) had their chest tubes removed in the OR, in 54% (62/114) of lobectomies, 62% (48/78) of segmentectomies, and 65% (20/31) of wedge resections. Thirteen patients (10%) required chest tube reinsertion, 11 after lobectomy and 2 after segmentectomy. The median operative time was 90 min (range 29–244 min), blood loss was 20 mL (range 10–60 mL), and all but one patient went home on postoperative day 1. No 30-day or 90-day mortality rate was recorded. A postoperative thoracentesis was performed in 1% of patients.ConclusionChest tubes can be safely removed in selective patients before they leave the OR after a robotic pulmonary resection with complete lymphadenectomy. Factors that may lead to these outcomes are the meticulous intraoperative technique and hemo-chylostasis. An air leak threshold of <20 mL/min may be optimal to minimize chest tube reinsertions and reduce failure rates.